Factors Related to the Selection of 1 Month Injecting Contraception in Age Couples Fertile (Pus) at Niar Maternity Home’s Percut Sei Master District Regency Deli Serdang - dessy sembiring (Institute of Computer Science (IOCS), 2022)
The high rate of use of 1-month injectable contraceptives does not indicate that 1-month injectable contraceptives are safe for acceptors, it showed that nationally the highest side effects were found in injectable contraceptives (44.9%). The purpose of this study was to determine the factors related to the selection of 1-month injectable contraceptives in Couples of Childbearing Age (PUS) at the Madina Maternity Home, Percut Sei Tuan District, Deli Serdang Regency. This research is analytical using primary data with a questionnaire data collection tool. The population of this study is the entire acceptor of birth control present in the Madina Maternity Home. Samples were taken by accidental sampling of 89 people. Data were analyzed univariate and bivariate with chi-square assay. From the results of research conducted based on the chi-square test with a meaningfulness level of 0.05, results were obtained that there was a relationship between the level of knowledge, education and work of respondents to the selection of injectable contraceptives 1 month with the results of calculate >tables, knowledge with count 16,313, education with count 7,413, and work with count 7,509. There was a significant association between respondents' level of knowledge and the selection of 1-month injectable contraceptives. It is hoped that the leadership of the Madina Maternity Home, especially the midwives at the Madina Maternity Home , will provide counseling on 1-month injectable contraceptives.